Autonomy, Gratification and R & D Outputs: A Small-Sample Field Study - Souder, William E. (Management Science, 1974)
Thirty-two research and development scientists working under high and low autonomy conditions were studied for differences in attitudes and behavior, and their (thirty-two) one-man projects were studied for differences in output levels. High autonomy development scientists were found to have higher levels of work gratification and interpersonal compatibility than their low autonomy counterparts. For research scientists, no such attitudinal and behavioral differences were found between high and low autonomy conditions. Development projects were found to have generally higher levels of outputs than research projects, where outputs were measured in terms of the percent technical problems solved and the project degree of achievement. However, for both research and development projects, the output levels did not vary with the degree of autonomy. Taken together, the detailed results indicate that the work orientation of a project, research or development, can have a significant influence on project outputs. By contrast, the degree of autonomy may only influence certain attitudinal and behavioral dimensions, which may be unrelated to output levels. These results are consistent with the conventional wisdoms, and their implications for management are largely in accord with modern management practices.